Water Accounting in Improving Irrigation Efficiency and Farmers’ Income Amid Limited Water Access in North Gorontalo City - Zulkifli Bokiu; Eduart Wolok; Hasyim Hasyim; Sahmin Noholo (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
This study aims to analyze the application of water accounting in supporting agricultural sustainability in North Gorontalo City, focusing on the issue of limited access to irrigation water faced by farmers. The scope of the research includes difficulties in obtaining water from irrigation channels due to sub optimal infrastructure, forcing farmers to rely on groundwater pumped at high cost. This condition directly increases production expenses and reduces farmers’ income. The study employs a descriptive qualitative approach, with data collected through field observations and in-depth interviews with farmers, irrigation managers, and relevant government officials. The collected data were analyzed thematically to identify the root causes and potential solutions for more efficient water management. The findings indicate that farmers urgently need a stable supply of water from irrigation channels to maintain crop productivity, particularly rice. The operational costs of groundwater pumping were proven to reduce farmers’ profit margins. Furthermore, there has been insufficient attention and no concrete steps from the local government to repair irrigation channels or provide alternative solutions. This study highlights the need for implementing a water accounting system as a basis for planning efficient water management, as well as encouraging active collaboration between the government and farmers to achieve sustainable agriculture.